DETERMINANTS OF MARKET PARTICIPATION AMONG SMALLHOLDER STAPLE CROP FARMERS IN OYO STATE, NIGERIA - OLADIRAN, J. O.; OGUNNIYI, L. T.; FANIFOSI, G. E. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
This study examined the determinants of market participation among smallholder staple farmers in Oyo state. Multistage sampling technique was employed to select 356 respondents. In the first stage, 40 villages were selected in the 4 zones according to the presence of food crops farmers. In the second stage, households were randomly selected based on whether they participate or not in cassava and yam production. Two percent of the registered farmers were proportionately selected based on the number of staple food farmers. Analytical technique employed included descriptive statistics and Ordered probit. Descriptive statistics was used to describe the quantitative data while Ordered probit model was used to analyse the factors influencing the market participation of cassava and yam farmers in the study area. The results showed that the mean age of the respondents was 46years, their mean household size was 5 and 11 years of formal education.  The mean years of experience was 19 years. The coefficients of age, gender and market information were statistically significant for net buyers, autarkic and net sellers of cassava. Similarly, for net buyers of yam, age, gender, household size, years spent in school and contract marketing, were statistically significant. Also, for autarkic and net sellers of yam, coefficients of age, gender, marital status, household size, years spent in school and contract marketing were statistically significant. It was concluded that the coefficients of age and gender significantly influenced a net buyer, autarkic and a net seller of cassava and yam respectively and recommended policy-makers to address the problem of market participation and level of participation among food crop farmers.